Reason enough to hope : America and the world of the twenty-first century - Morrison, Philip (MIT Press, 1998)
In this "blue-sky" effort to rethink humanity's basic challenges, Philip Morrison and Kosta Tsipis - both eminent scientists with deep expertise in arms control issues - sketch the broad outlines for a global approach to the problems of security and development. Their goal is to set priorities for feasible action, and their focus is threefold: war and particularly the continuing dangers of nuclear weapons, population and the promotion of increased levels of human well-being, and the threat of environmental degradation. -- Provided by publisher